Filter Cake and Vinasse as Fertilizers Contributing to Conservation Agriculture - Renato de Mello Prado; Gustavo Caione; Cid Naudi Silva Campos (Applied and Environmental Soil Science)
Utilising organic residues in agriculture contributes to the conservation of natural resources by recycling carbon and mineral elements. Organic residues produced by the sugar and alcohol agroindustries have great potential for use in conservation agriculture. The production of sugar and alcohol generates large quantities of byproducts, such as filter cake and vinasse, which can be used as soil improvers and substitutes for inorganic phosphorus and potassium fertilizers. However, the use of these residues in agriculture requires specific recommendations for each pedoclimatic condition to prevent environmental damage.